Media Sosial Instagram Sebagai Sarana Promosi Untuk Meningkatkan Minat Beli Konsumen (Studi Kasus Pada Mini Organic Mart Surabaya) - Yulianti, Risma; Yuliati, Nuriah; Andrian Syah, Mirza (Forum Agribisnis, 2025)
Mini Organic Mart is a retail business that offers quality healthy and organic products. Mini Organic Mart has been promoting using social media, especially Instagram, since 2016, but the way to attract consumer attention through social media is still limited. Based on a preliminary survey, the average number of "likes" on popular uploads is only around 15. For business accounts, this figure is relatively low. The aim of this research is to analyze the influence of promotions via social media, especially Instagram, on consumer buying interest. The analytical method used in this research is Crosstabulation and SEM-PLS analysis, especially through the WarpPLS 7.0 program. Primary data was obtained through distributing questionnaires via Instagram stories, samples were taken from 100 respondents via followers @jualprodukorganik_mom. The results of the research state that the promotions carried out by Mini Organic Mart through its Instagram account have a positive and significant influence on consumer buying interest.